An Analysis Of The Use Of Accounting System On Cloud: A Case Study In Abbaz Advisory. - Nur Hidayah Laili; Khairil Faizal Khairi; Rosnia Masruki (Kolej Universiti Islam Antarabangsa Selangor (KUIS), 2024)
Non-Indexed Publication